Disruption of Maize Kernel Growth and Development by Heat Stress (Role of Cytokinin/Abscisic Acid Balance). - Cheikh, N. (1994)
Temperature stress during kernel development affects maize (Zea mays L.) grain growth and yield stability. Maize kernels (hybrid A619 x W64A) were cultured in vitro at 3 d after pollination and either maintained at 25[deg]C or transferred to 35[deg]C for 4 or 8 d, then returned to 25[deg]C until physiological maturity. Kernel fresh and dry matter accumulation was severely disrupted by the long-term heat stress (8 d at 35[deg]C) and did not recover when transferred back to 25[deg]C, resulting in abortion of 97% of the kernels. Kernels exposed to 35[deg]C for 4 d (short-term heat stress) exhibited a recovery in kernel growth and water content at about 18 d after pollination and kernel abortion was reduced to about 23%. During the cell division phase, abscisic acid (ABA) levels showed a steady decline in the control but maintained a moderate level in the heat-stressed kernels. However, later in development heat-stressed kernels had significantly higher levels of ABA than the control. Cytokinin analysis confirmed a peak in zeatin riboside and zeatin levels in control kernels at 10 to 12d after pollination. In contrast, kernels subjected to 4 d of heat stress had no detectable levels of zeatin and the zeatin riboside peak was reduced by 70% and delayed until 18 d after pollination. The long-term heat-stressed kernels showed low to nondetectable levels of either zeatin riboside or zeatin. Regression analysis of ABA level against cytokinin level during the endosperm cell division phase revealed a highly significant negative correlation in nonstressed kernels but no correlation in kernels exposed to short-term or long-term heat stress. Application of benzyladenine to heat-stressed, growth-chamber-grown plants increased thermotolerance in part by reducing kernel abortion at the tip and middle positions on the ear. These results confirm that shift in hormone balance of kernels is one mechanism by which heat stress disrupts maize kernel development. The maintenance of high levels of cytokinins in the kernels during heat stress appears to be important in increasing thermotolerance and providing yield stability of maize.